1983
DOI: 10.1172/jci111045
|View full text |Cite
|
Sign up to set email alerts
|

Guanine nucleotides modulate the binding affinity of the oligopeptide chemoattractant receptor on human polymorphonuclear leukocytes.

Abstract: A B S T R A C T The oligopeptide chemoattractant receptor on human polymorphonuclear leukocyte (PMN) membranes exists in two affinity states. Since guanine nucleotides regulate the binding affinity and transductional activity of several other types of receptors, we examined the effect of nucleotides on the binding of N-formyl-methionyl peptides to their receptors on human PMN membranes. The addition of guanylylimidodiphosphate (0.1 mM), a nonhydrolyzable derivative of guanosine triphosphate (GTP), to PMN membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(75 citation statements)
references
References 13 publications
6
68
0
1
Order By: Relevance
“…This effect is due to a reduction in the number of high affinity peptide binding sites. These findings are qualitatively similar to those obtained by Snyderman and colleagues who studied the effect of guanine nucleotides on binding of fMet-Le~-[~H]Phe to membranes of human peripheral neutrophils [20]. However, there are important quantitative differences between the two systems.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This effect is due to a reduction in the number of high affinity peptide binding sites. These findings are qualitatively similar to those obtained by Snyderman and colleagues who studied the effect of guanine nucleotides on binding of fMet-Le~-[~H]Phe to membranes of human peripheral neutrophils [20]. However, there are important quantitative differences between the two systems.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, increasing the amount of MgCI2 added to the binding reaction from 0 to 1.5 mM and 5 mM MgC12 resulted in a 4.4-fold and 8.9-fold increase in the number of high affinity receptors, respectively, whereas the number of low affinity receptors appeared to remain largely unaltered. Binding of formyl peptides to membranes prepared from human peripheral neutrophils has previously been noted to be modified by guanine nucleotides [20]. We therefore determined the role of guanine nucleotides in regulating the Mg2+-stimulated binding of fMet-Le~-[~H]Phe to HL 60 membranes.…”
Section: Resultsmentioning
confidence: 99%
“…A number of small molecules was discovered in the 60's and 70's, including activated complement C5a and N-formylated peptides of bacterial origin [2][3][4] . Evidence that these "classic chemoattractants" act on GPCRs first came from the observation that pertussis toxin (PTX) could alter the binding affinity of chemotactic formyl peptides [5] , a characteristic feature of certain GPCR ligands [6] . Working independently, two laboratories reported that PTX could block formyl peptide (eg, fMet-Leu-Phe, fMLF)-induced neutrophil functions through ADP-ribosylation of the Gi class of heterotrimeric G proteins [7,8] .…”
Section: Gpcrs That Mediate Cell Migration and Phagocyte Activationmentioning
confidence: 99%
“…Binding studies with neutrophils (Koo et al, 1982) and macrophages (Snyderman et al, 1984) demonstrated a single class of binding sites, with a Kd close to 20nM. Upon cell disruption, high-affinity receptor sites with a Kd of 1-2 nM were unmasked (Koo et al, 1982;Mackin et al, 1982;Snyderman et al, 1984; for review, see Snyderman et al, 1986 and.…”
Section: The Early Steps In the Signaling Pathwaymentioning
confidence: 99%